Uso de tecnologías móviles aplicadas a la enseñanza de proyecciones ortogonales en el curso expresión gráfica I (2019)
Graphic expression course I seeks to train engineering students so that they can communicate through drawing. The development of spatial skills is fundamental to fulfill this objective. However, sorne students have difficulties with traditional teaching, therefore, it is proposed to implement easy-to-access teaching tools by applying virtual three-dimensional models which can be viewed and manipulated on mobile devices through applications of either augmented reality ar visualization to support students with problems in the development of spatial skills ar far those who wish to deepen the subject. The proposed models were made in a computer-aided design program; these models can be linked to markers using an augmented reality application ar sent directly to the student's phone. During the implementation, a website was used as a repository and a physical guide explaining the use of the tool, achieving not only a better understanding of the tapies exposed in class but also arousing the student's interest in information technologies and communication.